PENERAPAN METODE CTL (CONTEXSTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA.1 SMA NEGERI JENGGAWAH MELALUI PEMBUATAN MODEL STRUKTUR SEL 3D - An Rini Mudayanti (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2021)
The research application of CTL (contextual teaching and learning) method through making of 3D cell model aims to determine the effect on student's motivation, learning outcomes and to find out the understanding student concepts. For this reason, it is necessary to have a PTK with 2 cycles. The subjects of this research were students of SMA Negeri Jenggawah especially class XI IPA.1 which consisted of 36 students with 12 male and 24 female. The data analysis used is standards descriptive statistical of data analysis. The results of this research indicate that the application of CTL method through making of 3D cell models has a significant impact on student motivation and learning outcomes. Indicated by an increase in student learning motivation, so that it affects learning outcomes from pre-cycle to cycle 2 by 69%. There were 25 students who obtained very good criteria and an increase in classical learning outcomes of 86.11% (31 students who completed) with an average score of 79.83 = 80 and the highest score was 98 while the lowest score was 68.